Elastic fracture mechanics analysis of bi-materials using boundary element method - Yong, Owe Hong Zheng (Nanyang Technological University, 2022)
Bimaterial interfacial cracks in two isotropic elastic half plates that have different Young Modulus was investigated. The influence of circular hole with inclusions on the interfacial cracks tip stress intensity factor was also analysed. Tensile loadings acting on the matrix and orientated perpendicular to the direction of the crack length was evaluated. The multi-region boundary element method (BEM) using quadratic quarter-point crack-tip element, commonly known as Quarter Node Shift (QNS) was employed in modelling the crack. The interaction of the circular inclusion may induce propagating or shielding effects on the SIF of the crack tip, which depends on variable parameters, namely the relative elastic properties of the matrices, angular orientation of inclusion, geometry of circular inclusion, distance of the circular inclusion from the crack tip and also in the cases where the matrix are subjected to biaxial loadings.